Sub Saharan Africa feeds database - International Livestock Research Institute (International Livestock Research Institute, 2006)
SSA Feeds' is a web-based software and associated database that provides information on the nutritive value of feedstuffs used in sub-Saharan Africa (SSA). It is intended for extension, Development and research agents to design scientifically-based feeding systems for meat, dairy and draught animals. Better nourished livestock improve food security and income of small-scale African farmers. It is divedide in 9 sections, viz, herbaceous forages; fodder trees and shrubs; food crops: cereals & legumes, and residues; food crops: tubers, and roots; food crops: others; concentrate feeds and agro-industrial by-products; mineral supplements; and other less common feeds.